2013
DOI: 10.1097/dcr.0b013e318294ed6b
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of Bowel Obstruction in Patients with Stage IV Colon Cancer

Abstract: BACKGROUND Bowel obstruction is a common complication of late-stage abdominal cancer, especially colon cancer, which has been investigated predominantly in small, single-institution studies. OBJECTIVE We used a large, population-based data set to explore the surgical treatment of bowel obstruction and its outcomes after hospitalization for obstruction among patients with stage IV colon cancer. DESIGN This was a retrospective cohort study. SETTING AND PATIENTS We identified 1004 patients aged 65 years or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…This survival benefit was coupled with more post-obstruction time spent in the hospital, such that percent of life after obstruction spent in the hospital was equivalent between surgical and non-surgical groups, consistent with a trend we previously observed examining obstruction outcomes in the context of stage 4 colon cancer[37]. In that study, as in this, surgery’s survival benefit was no longer significant after adjusting for adhesive etiology, consistent with suggestions that the apparent benefits of surgery may be due to factors leading to selection for surgery[6, 11].…”
Section: Discussionsupporting
confidence: 86%
“…This survival benefit was coupled with more post-obstruction time spent in the hospital, such that percent of life after obstruction spent in the hospital was equivalent between surgical and non-surgical groups, consistent with a trend we previously observed examining obstruction outcomes in the context of stage 4 colon cancer[37]. In that study, as in this, surgery’s survival benefit was no longer significant after adjusting for adhesive etiology, consistent with suggestions that the apparent benefits of surgery may be due to factors leading to selection for surgery[6, 11].…”
Section: Discussionsupporting
confidence: 86%
“…Up to 65% of stage IV CRC patients had symptoms of tumor complications such as intestinal obstruction, perforation, intractable pain, and bleeding [10]. The most common symptom of patients with stage IV CRC is intestinal obstruction with rates of 7% to 29% [20,21] Because of the more advanced status of the patients in our study, we observed a higher incidence (37.2%) of intestinal obstruction. Non-operative methods including endoscopic stenting or laser recanalization have generally been advocated for patients with poor performance status and/or advanced age in order to reduce the morbidity and mortality associated with surgery.…”
Section: Discussionmentioning
confidence: 47%
“…An accompanying report focuses on the treatments during and outcomes after hospitalization for BO. 49 …”
Section: Discussionmentioning
confidence: 99%